Stealing Kathryn - Frank, Jacquelyn (Frank, Jacquelyn. Gatherers., 2010)
Adrian uses his powers over the realm of sleep to reap the dark energy of nightmares until he meets Kathryn, a woman he risks everything to obtain, not realizing that she has the power to save him or destroy them both.